(untitled) (Bangladesh Journal of Medical Microbiology, 2012)
A case-control study was carried out in the Department of Microbiology & Immunology at BSMMU, Dhaka from July 2007 to June 2008 to validate IgM flow assay commercial diagnostic kits to assess the usefulness for the rapid diagnosis of typhoid fever. A total of 437 febrile patients clinically suspected of having typhoid fever were studied. Sixty cases were taken as controls, in which 30 were febrile controls (non-typhoidal febrile illness) and 30 were healthy controls. Among these 437 patients, Salmonella typhi was isolated from 58 (13.27%) cases .The isolation rate of S.typhi from blood was higher 21 (22.34%) in pediatric age group than that of the adult 37(10.78%); which is statistically significant (P<0.003).The detection of specific LPS antibody (IgM flow assay) were evaluated in 58 culture proven cases,42 high Widal titre patients and 60 controls. The sensitivity of LPS antibody and Widal test was 91% and 54% respectively and specificity was 100% and 91.66% respectively. The serological assays based on the detection of IgM antibodies against serotype Typhi LPS had a significantly higher sensitivity and specificity than Widal test when used with a single acute phase serum sample(P<0.007). So, these test involving detection of anti-LPS antibodies could be of use for the diagnosis of typhoid fever in patients who have clinical typhoid fever but are negative in culture or in regions where bacterial culturing facilities are not readily available. DOI: http://dx.doi.org/10.3329/bjmm.v6i1.19362 Bangladesh J Med Microbiol 2012; 06(01): 18-21